SOME CLASSIFICATIONS OF MONOIDS BY VARIOUS NOTIONS OF INJECTIVITY OF ACTS - M. Roueentan; M. Ershad; M. A. Naghipoor (Journal of Algebraic Systems, 2021)
This paper is a continuation of recent researches concerning generalization of injectivity of acts over moniods, namely, C-injectivity and InD-injectivity. We introduce new kinds of injectivity, such as, LC-injectivity and CQ-injectivity. Classifications of monoids by properties of these kinds of injective acts are presented. It is proved that a monoid S is completely (cyclic) injective if and only if it is completely quasi (CQ-) injective. Some results on quasi-injective acts are proved. Also new characterizations for right hereditary monoids and right PP-monoids are given.